Why Pakistani small and medium enterprises are not reporting on sustainability practices? - Zeeshan Mahmood; Rehana Kouser; Ibn e Hassan; Zeeshan Iqbal (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
This paper seeks to understand why Pakistani SMEs are not reporting on sustainability practices. Also, this paper aims to understand the sustainability reporting patterns of SMEs worldwide. Out of 190 sustainability reports, published by SMEs around the world, there is not even a single report published by any Pakistani SME. This paper employs mixed methodology that includes the use of quantitative content analysis for understanding the reporting patterns and the use of questionnaire based survey and qualitative interviews for understanding the reasons for non-reporting. This paper concludes that there is a lack of awareness about sustainability reporting. Also, there are some implementation issues, lack of training and skills, lack of regulation, government support and sustainability infrastructure. Furthermore, the stakeholder pressure and demand for sustainability reporting is missing in the context of Pakistan. In the absence of all these pressures and in the presence of limited resources, SMEs are least interested in sustainability reporting as perceived benefits are far less than perceived costs.
Keywords: 330; sustainability practices; sustainability reporting; small & medium enterprises; Pakistan; non-reporting sustainability